IMPLEMENTATION OF QUALITY MANAGEMENT IN ISLAMIC RELIGIOUS EDUCATION LEARNING - Warsono Warsono; Sriyanto Sriyanto; Nasrudin Harahap; Nurul Hidayati Murtafiah (Al Wildan: Jurnal Manajemen Pendidikan Islam, 2022)
This study aims to analyze the implementation of quality management in Islamic religious education learning as well as the supporting and inhibiting factors. This research is descriptive qualitative. Data was collected through interviews, observation, and documentation. The data were analyzed by means of data reduction, data presentation, and conclusions. The results of the analysis 1) are summarized in the preparation of effective week plans, mapping SK/KD, KKM, annual programs, semester programs, syllabus, and lesson plans, (2) applying interesting media, carrying out extracurricular activities, (3) teachers providing media and learning equipment form the authority to coordinate learning in the classroom, participate in training, (4) the teacher supervises learning activities in the classroom, evaluates the results of the implementation of learning, supervising in the evaluation process in the form of tests or assignments. (5) Prepare questions/assessment tools, carry out assessments, check answers, assess learning outcomes, manage learning outcomes, analyze learning outcomes, conclude assessment results clearly and logically, compile reports on learning outcomes, and improve assessment questions/tools. Supporting factors (1) increased time allocation, (2) training assistance, (3) good relations between teachers, (4) school principal support for teachers, (5) teacher supervision, and (6) supervision by school school principals. In contrast, the inhibiting factors are (1) the lack of learning facilities and media, (2) the lack of innovation in the preparation of learning plans, and (3) the lack of student practice outside of school.